2014
DOI: 10.1016/j.csbj.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Variations in metabolic pathways create challenges for automated metabolic reconstructions: Examples from the tetrahydrofolate synthesis pathway

Abstract: The availability of thousands of sequenced genomes has revealed the diversity of biochemical solutions to similar chemical problems. Even for molecules at the heart of metabolism, such as cofactors, the pathway enzymes first discovered in model organisms like Escherichia coli or Saccharomyces cerevisiae are often not universally conserved. Tetrahydrofolate (THF) (or its close relative tetrahydromethanopterin) is a universal and essential C1-carrier that most microbes and plants synthesize de novo. The THF bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Additionally, gene annotations are lacking or unspecific and/or the associated pathways are not accounted for by the automated reconstruction pipelines, resulting in a less predictive draft reconstruction. Moreover, even universal pathways vary in the enzymes carrying out individual steps . As a result, annotation platforms often fail to correctly reconstruct these variant pathways .…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, gene annotations are lacking or unspecific and/or the associated pathways are not accounted for by the automated reconstruction pipelines, resulting in a less predictive draft reconstruction. Moreover, even universal pathways vary in the enzymes carrying out individual steps . As a result, annotation platforms often fail to correctly reconstruct these variant pathways .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Moreover, even universal pathways vary in the enzymes carrying out individual steps . As a result, annotation platforms often fail to correctly reconstruct these variant pathways . Several recent comparative genomics studies have resulted in the improvement of genome annotations in gut microbial genomes .…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is expected that these strains are not auxotrophic for folates or DHP but can produce folate in the presence of PABA supplementation.The presence/absence of the components of the folate biosynthesis pathway is reported based on KEGG pathway analysis. Previous studies have revealed that B. subtilis genome harbor all the pathways components and have been engineered for folate production[63,65,66].…”
mentioning
confidence: 99%
“…2.A.88) (4) or a member of the folate-biopterin transporter (FBT) family present in protists, cyanobacteria, and plants (TC no. 2.A.71) (5)(6)(7)(8)(9). Once inside the cell, folate is reduced via DHF reductase (FolA) to DHF and then to THF (Fig.…”
mentioning
confidence: 99%